1973
DOI: 10.1037/h0034462
|View full text |Cite
|
Sign up to set email alerts
|

Credibility and desirability of positive and negative structured feedback in groups.

Abstract: This study examined three different sequences of positive and negative feedback delivered in T groups. The Ss were 46 undergraduates. The believability and desirability of the feedback, as rated by the 5s who received the feedback, were the main areas of interest. Positive feedback was found to be more desirable and tended to be more believable than negative feedback. Overall, the sequence of negative feedback delivered first, followed by later positive feedback, was more effective than positive feedback follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…Items on the Evaluative factor conveyed a similar negative emotional tone and focused specifically on feelings about being evaluated. The tone of the items which loaded on the Feelings and Evaluative factors reflects the strong prohibition against giving feedback in our society (Jacobs, Jacobs, Gatz, & Schaible, 1973;Yalom, 1983). These observations cause us to think that leaders will need to carefully attend to members' fears that giving corrective feedback will damage interpersonal relationships and possibly result in rejection.…”
Section: Emotional Barriersmentioning
confidence: 99%
“…Items on the Evaluative factor conveyed a similar negative emotional tone and focused specifically on feelings about being evaluated. The tone of the items which loaded on the Feelings and Evaluative factors reflects the strong prohibition against giving feedback in our society (Jacobs, Jacobs, Gatz, & Schaible, 1973;Yalom, 1983). These observations cause us to think that leaders will need to carefully attend to members' fears that giving corrective feedback will damage interpersonal relationships and possibly result in rejection.…”
Section: Emotional Barriersmentioning
confidence: 99%
“…Also, sexual attraction lures us all to partake in the propagation of our species. Braaten (1987aBraaten ( , 1987bBraaten ( , 1988 Yalom & Rank (1966) Support and Caring Bednar & Lawlis (1971) Bednar et al (1974) Braaten (1987a, 1987b, 1988 Yalom et al (1967) Zimpfer (1967 Listening and Empathy Bednar & Lawlis (1971) Bednar & Kaul (1978) Braaten (1987b, 1988) Budman et al (1987) Dies (1983) Gendlin (1979) Hurst et al (1978) Jacobs (1977) Jacobs et al (1973a, 1973b MacKenzie (1983) Self-Disclosure and Feedback Beck (1974) Bednar & Lawlis (1971) Bednar et al (1974a) Bloch et al (1981) Braaten (1986) Crews & Melnick (1976 Dies(1973Dies( , 1977Dies( , 1983 Yalom & Rand (1966) Finally, modern man is often lonely and alienated from comrades. In my experience, it is helpful to keep these undercurrents in mind to understand why a carefully designed group format is so attractive.…”
Section: Attraction and Bondingmentioning
confidence: 99%
“…These papers also studied group cohesiveness. Although Jacobs et al (1973b) obtained no significant relation between cohesiveness and feedback valence, Jacobs et al (1973a) discovered that group cohesiveness was significantly greater in groups using positive feedback than in groups using negative feedback. Schaible and Jacobs (1975) refined this conclusion in their study of sequences of feedback statements.…”
mentioning
confidence: 91%
“…A series of papers investigating the effect of the valence of feedback statements (Jacobs et al, 1973a(Jacobs et al, , 1973bSchaible and Jacobs, 1975) concluded that positive feedback was more desirable and more believable than negative feedback. These papers also studied group cohesiveness.…”
mentioning
confidence: 99%